Pengaruh Pembelajaran Inkuiri Terbimbing Berkonteks Socio-Scientific Issues (SSI) terhadap Literasi Kimia dan Kesadaran Lingkungan Siswa pada Materi Laju Reaksi - Muhammad Hisyam; Sri Handayani (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the influence of guided inquiry learning contextualized with SSI on students' chemistry literacy and environmental awareness. This research is a quasi-experimental research with a non-equivalent (pre-test and post-test) control-group design. This research was conducted at SMA N 111 Jakarta and SMA N 41 Jakarta. The research sample consisted of 132 eleventh-grade students. The sampling technique used was cluster random sampling. The instruments used in this study consisted of a chemistry literacy test and an environmental awareness questionnaire. The data analysis technique used is multivariate statistics, specifically employing the MANOVA test. The research findings indicate that there are significant differences in students' chemical literacy and environmental awareness when implementing the guided inquiry learning contextualized with SSI. Overall, the impact of guided inquiry learning contextualized with SSI provides an effective contribution of 24.4% to students' chemical literacy and environmental awareness.